2003
DOI: 10.1292/jvms.65.1195
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Iodoacetate-Induced Experimental Osteoarthritis and Associated Pain Model in Rats

Abstract: ABSTRACT. Degenerative lesions were induced in the knee joint of Wistar rats by intraarticular injection of chondrocyte metabolism inhibitor mono-iodoacetate (MIA) at doses of 0, 0.3 or 3 mg/joint. Histopathological examination and the measurement of hind paw weight ratio as an index of joint pain by incapacitance tester were performed. Histological findings that are similar to those observe d in human osteoarthritis (OA), such as disorganization of chondrocytes, erosion and fibrillation of cartilage surface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
99
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(104 citation statements)
references
References 15 publications
5
99
0
Order By: Relevance
“…These results are similar to those of the previous study about the rat model of knee OA. MIA has been shown to inhibit chondrocyte metabolism and promote apoptosis [15], and its injection was found to induce various histological changes similar to those in human OA [15,16]. Kobayashi et al [16] reported that an intra-articular injection of MIA induced OA-like histopathologic changes and a loss of proteoglycan from cartilage tissue in the knee joint in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are similar to those of the previous study about the rat model of knee OA. MIA has been shown to inhibit chondrocyte metabolism and promote apoptosis [15], and its injection was found to induce various histological changes similar to those in human OA [15,16]. Kobayashi et al [16] reported that an intra-articular injection of MIA induced OA-like histopathologic changes and a loss of proteoglycan from cartilage tissue in the knee joint in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…MIA has been shown to inhibit chondrocyte metabolism and promote apoptosis [15], and its injection was found to induce various histological changes similar to those in human OA [15,16]. Kobayashi et al [16] reported that an intra-articular injection of MIA induced OA-like histopathologic changes and a loss of proteoglycan from cartilage tissue in the knee joint in a dose-dependent manner. A MIAinduced model of knee OA was established and has been used in some studies [7][8][9][10]15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injection of MIA in the knee joint induces necrosis of chondrocytes with decrease of cartilage thickness and osteolysis [19]. Kobayashi et al showed that MIA is able to disorganize chondrocytes and to promote cartilage erosion [20]. These alterations are comparable with joint damages typical of humans affected by osteoarthritis [21e23].…”
Section: Chemistrymentioning
confidence: 99%
“…Histopathological changes in each animal were quantitatively expressed by three grades for each finding. 14) Grading was done under the authority of Medplan Pathology Laboratories, Seoul, Korea.…”
Section: Protective Effects Of Human Placenta Extract On Cartilage Dementioning
confidence: 99%